Participação do fornecedor de ingredientes no desenvolvimento de produtos: estudo de casos em processadoras de bebidas. - Onoyama, Marcia Mitiko (Universidade Federal de São Carlos, 2006)
The capacity of introducing new products in the market has been considered as an important factor for companies competitiveness. This is the reality of the food industry that adopts technological and organizational changes in their productive processes, the materials supply and the products distribution, mainly for products differentiation. These changes evidence the suppliers and distributors growing to the food processed supply chain. Then, the importance of this study: its contribution for the understanding of the supplier s paper in the new beverage development process. Besides, the researched theme has relevance considering the shortage of works that analyze the relationship of ingredients suppliers in the food chain. It is had as presupposition, based on the literature, that the supplier involvement in the product development process propitiates time and cost reduction in the product development, quality improvement of the acquired materials and larger access facility and technology application. The analysis of the suppliers involvement in the supply chain focused in their participation in the buyer s new product development process, narrowing to the ingredients suppliers. This work was developed with multiple cases studies in four companies of the segments of no alcoholic drinks (fresh juice and powdered soft drinks) and drunk milky and a common ingredient supplier to those companies. Those segments were chosen due to the great growth of the demand by these products, given the appeal of their functional (health) and convenience (comfort). It was observed, mainly, that the responsibility degree of the supplier in the product development is function of its technical competence (knowledge and experience). It was also verified that the supplier s participation that happens in the initial phases of the new beverage process development, facilitates the access and technology application in the food product development process.
Keywords: Desenvolvimento de novos produtos; Fornecedores; Alimentos - indústria; New product development; Ingredient suppliers; Food industry; Supplier involvement in the product development; ENGENHARIAS::ENGENHARIA DE PRODUCAO